Intellectual Capital and Risk Management to Overcome Non Performing Loans - Azmi, Fika; Kurniawan, Pratomo Cahyo (Jurnal Analisis Bisnis Ekonomi, 2021)
The implementation of risk management is an obligation that must be carried out by rural banks in every business activity in accordance with Financial Services Authority regulation 13/OJK.03/2015. This study aims to examine whether the implementation of risk management can strengthen or weaken the effect of intellectual capital on non-performing loans. The sampling method used the saturated method and obtained data of 26 research samples. The selected respondents were the leaders of the rural banks in Semarang City. Data analysis using Moderated Regression Analysis (MRA) shows that intellectual capital has a negative effect to non-performing loans. Furthermore, the implementation of risk management strengthens the relationship between intellectual capital and non-performing loans. This means that optimal management of intellectual capital and supported by effective risk management will reduce non-performing loans